Epistemology Of Ahmad Sirhindi's Interpretation In The Book Of Mektubat Rabbani - Abdurrahman, Hafiz; Sukiman (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Epistemological changes can also affect the development of interpretation depending on the nature of science, the social context and the time in which the interpreter is located. Currently, not only philosophy, epistemological problems also spread to other disciplines such as interpretation. This study analyzes the epistemology of Ahmad Sirhindi's interpretation in the book Mektubat Rabbani to find out the sources used in the interpretation, the methods used to conduct the analysis, the patterns produced from the analysis, and the validity of the results of the analysis. This research is a qualitative research that uses a content analysis model and the type of library research related to books, journals, and others. The results obtained from this study include the integration between interpretation bil ma'tsur which is sourced from the Qur'an and hadith with interpretation bil ra'yi which shows the personal opinions of the interpreter, with this the book Mektubat Rabbani falls into the category of interpretation bil iqtirani when viewed from the source of interpretation. The interpretation made by Ahmad Sirhindi using many parameters and characteristics can be included in the category of Isyari Interpretation according to its method. The most dominant style of this interpretation is shufi, as well as kalami, fiqhi, siyasi and falsafi. Ahmad Sirhindi's Mektubat Rabbani is based on pragmatic theory, which presents solutions to the problems and confusion faced by society